Menganalisis Kebijakan Kesejahteraan Guru Honorer Terhadap Peningkatan Kualitas Pendidikan di SMKN 1 Driyorejo - Rizqia Rachmi, Alfie; Febrianti Zahroh, Icha; Puspita Ribiana, Alyadea; Windasari, Windasari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
This study utilized a case study of non-permanent and permanent teachers at SMKN 1 Driyorejo. This study employed a qualitative approach. Needs analysis, vacancy announcements, application acceptance, selection, and signing of employment contracts were all part of the open and transparent recruitment process for non-permanent teachers. With the Teacher and Lecturer Law and the Regional Government Law, the government is responsible for the welfare of non-permanent teachers; however, further policies are needed, such as salary guarantees, training, employment contracts, legal protection, certification, budgets, and welfare benefits. The principal of SMKN 1 Driyorejo implemented a good leadership style; there was no distinction between non-permanent and permanent teachers; provided motivation, training, seminars, and performance evaluations; and ensured that non-permanent teachers had official appointment letters and information on civil servant recruitment. Issues faced by non-permanent teachers, such as short-term employment contracts and compensation, can be overcome to improve the welfare of non-permanent teachers.